Why do individuals agree to enrol in clinical trials? A qualitative study of health research participation in Blantyre, Malawi. - Mfutso-Bengo, J; Ndebele, P; Jumbe, V; Mkunthi, M; Masiye, F; Molyneux, S; Molyneux, M (2008)
Current literature suggests that therapeutic misconception a belief by participants in a clinical trial that they are in fact simply being given clinical care is common, especially among illiterate populations in developing countries. Therapeutic misconception reects problems in informed consent, as people agree to participate in clinical trials without being aware that the trial procedures and test products may not in fact benet them. In this study of Malawian adults who had participated in research projects of various kinds during the preceding years, we found that the majority participated in research for the sake of obtaining better quality treatment made available through the clinical trials as ancillary care. Their consent to participate was not due to a belief that the actual procedures of the trial would directly benet their health. Respondents indicated that, government hospitals being crowded and commonly lacking drugs, they agreed to take part in research projects in the hope of obtaining access to ancillary care provided by clinical trials. We conclude that in this environment, possibly owing to inadequacy of routine health services, people make rational decisions to participate in research. We question whether the term therapeutic misconception accurately describes participants motivation under conditions of limited resources. We also discuss the relevance of these ndings for understanding undue inducement in clinical trials.